Improvement of POC-CCA Interpretation by Using Lyophilization of Urine from Patients with Schistosoma mansoni Low Worm Burden: Towards an Elimination of Doubts about the Concept of Trace. - Paulo Marcos Zech Coelho; Liliane Maria Vidal Siqueira; Rafaella Fortini Queiroz Grenfell; Nathalie Bonatti Franco Almeida; Naftale Katz; Áureo Almeida; Nídia Francisca de Figueiredo Carneiro; Edward Oliveira (Public Library of Science (PLoS), 2016)
BACKGROUND:Accurate diagnostic techniques for schistosomiasis are essential for prevalence determination and identification of positive patients. A point-of-care test for detecting schistosome circulating cathodic antigen (POC-CCA) has been evaluated for its accuracy in different endemic regions. This reagent strip/dipstick based assay has showed high sensitivity for individuals with high or moderate worm burden, but the interpretation of light infections is less clear, especially for trace readings. METHODOLOGY/PRINCIPAL FINDINGS:We introduced a urine lyophilization step to the POC-CCA assay to improve its sensitivity and clarify the interpretation of traces. We evaluated POC-CCA sensitivity and specificity within individuals with low parasite burdens in a Brazilian endemic area where a high number of traces were detected. Patients that were positive for other helminths were also evaluated for cross reactions. In all cases, a combined parasitological diagnosis using Kato-Katz (24 slides) and Saline Gradient (1 g of feces) were used as reference. At baseline, diagnosis by POC-CCA (1-2 cassettes) showed 6% sensitivity, inaccurately predicting a low prevalence of Schistosoma mansoni infections (2 POC-CCA positives/32 egg positives). After urine lyophilization, the sensitivity was increased significantly (p < 0.05). Prevalence rates changed from 2% to 32% (27 POC-CCA positives/32 egg positives), equivalent to parasitological techniques. Most of the trace readings changed to positive after lyophilization while some negatives turned into traces. Cross reaction analysis confirmed the specificity of POC-CCA. CONCLUSIONS/SIGNIFICANCE:Trace readings cannot be primarily defined as positive or negative cases. It is critical to verify case-by-case by concentrating urine 10 fold by lyophilization for the diagnosis. Following lyophilization, persistent trace readings should be read as negatives. No trained technician is needed and cost is restricted to the cost of a lyophilizer and the electricity to run it.